Extreme Heat Kills Even in Very Hot Cities: Evidence from Nagpur, India - Priya Dutta (The International Journal of Occupational and Environmental Medicine, 2020)
Background: Although many studies have provided evidence for all-cause mortality attributed to extreme temperature across India, few studies have provided a systematic analysis of the association between all-cause mortality and temperature.